PERLINDUNGAN HAK MASYARAKAT ADAT DALAM PENGELOLAAN SUMBER DAYA ALAM BIDANG PERTAMBANGAN DI SUMATERA BARAT - Danel Aditia Situngkir (Ensiklopedia Research and Community Service Review, 2026)
Abstract: Mining Business Permit (IUP) does not include land rights, so anyone who will carry out mining in a mining area must first ensure the legal status of the land used. After knowing the legal status of the land, then can proceed with negotiations or agreements on matters that need to be agreed upon by the parties who promised that give rise to rights and obligations. Other things that serve as the basis are the decisions of the constitutional court and Law Number 23 of 2014 concerning Regional Government in the context of licensing. The provincial government has now taken over the authority of the district/city government to issue mining permits based on Law Number 23 of 2014 which is actually still semi-centralized and territorially in the context of mining is still in the district, while the provincial government is a representative of the central government. The policy of managing mining resources from the perspective of indigenous legal communities that is ecologically just lies in the concept of indigenous legal community wisdom in managing natural resources, in this case mining which is the right of control of the state. There is a reciprocal relationship between humans and nature, where customary law communities always place the balance of nature in environmental management, so that ecological justice can be felt by all elements of nature, apart from humans.Keywords: Protection, Rights of Indigenous Peoples, Natural Resources